Influence of selected aspects of local governance on the efficiency of waste collection and street cleaning services. (1st May 2021) - Benito, Bernardino; Guillamón, María-Dolores; Martínez-Córdoba, Pedro-José; Ríos, Ana-María
Highlights: Local governments (LGs) with greater citizen participation are more efficient in waste collection. More transparent LGs are less efficient in the provision of the street cleaning. Public management of the waste collection and street cleaning is more efficient. In waste collection, higher population density translates into improved efficiency. Tourist municipalities are less efficient in providing waste collection services. Abstract: Currently, in all developed countries there is great interest in improving democratic practices in local governments, as the administration closest to citizens. However, the possible influence of these actions on the management of public services and municipal finances have been side-lined, despite the great interest in evaluating the performance of local governments under budgetary constraints. Our research aims to fill this knowledge gap by studying the impact of key aspects of local governance (transparency and citizen participation), together with other environmental variables, on the efficiency of two municipal public services of both qualitative and quantitative importance: waste collection and street cleaning. The results show that the type of management, population density, the tourist activity of the municipality and the strength of local government are determinants that explain the efficiency of the public services examined in this research, while transparency and citizen participation have little impact.